The Symbolic Realm of Italian Migrants' POST-WWII HOUSES in Australia. (2nd September 2017) - Faggion, Laura; Furlan, Raffaello
Abstract: The Post-WWII period witnessed a large immigration flow of Italians towards Australia. This was facilitated by the assisted passage scheme funded by the Italian and Australian governments. Italian migrants, as well as diverse migrant groups, brought with them cultural practices and a way of life, which are nowadays part of the multicultural Australian society. Namely, it is argued that first-generation Italian migrants' houses are embedded by cultural meanings. Therefore, this research study investigates the symbolic realm of Post-WWII domestic dwellings built by Italian migrants in Brisbane, that is, the various meanings they associated with their homes. The data was collected from focus group discussion and in-depth interviews held at the Italian Club in Newmarket and at the residences of forty Veneto first generation migrants, who migrated to Australia in the Post-WWII period. The collected data has been subjected to thematic and to hermeneutic analysis. This procedure generated a list of various meanings embedded onto migrants' houses in Brisbane. The revealed findings contribute (1) to explore a historically significant process of Australian domestic architectural development and (2) to expose the symbolic realm preserved into the built environment, which represent the national cultural heritage of Australia.